Diversity and Potential of Nitrogen-Fixing Rhizosphere Bacteria Associated with Foxtail Millet (Setaria italica L.) as Candidates for Biofertilizers in Sustainable Agriculture - Yusril, Yusril; Muis, Nurmuliayanti; Wahid, Masyitha; Sari, Arlinda Puspita (Indonesian Journal of Ecology and Conservation, 2024)
Foxtail millet (Setaria italica L.) is a potential cereal crop that can be developed as an alternative food source. Rhizosphere microorganisms, particularly nitrogen-fixing bacteria, play an important role in improving soil fertility through nitrogen fixation and the production of plant growth hormones. However, information regarding the potential of rhizosphere bacteria associated with foxtail millet in West Sulawesi remains limited. This study aimed to isolate, select, and identify nitrogen-fixing rhizosphere bacteria associated with foxtail millet and to evaluate their potential as biofertilizer candidates. Bacterial isolation was conducted using a serial dilution method on selective Jensen medium, followed by colony morphology characterization and Gram staining. Selected isolates were further tested for their nitrogen-fixing ability and their capacity to produce plant growth hormones, including indole-3-acetic acid (IAA) and gibberellin (GA₃). Molecular identification was performed using 16S rRNA gene analysis. The results showed that 31 bacterial isolates were successfully obtained from the rhizosphere of foxtail millet, of which 10 isolates were selected based on morphological characteristics. Five isolates demonstrated nitrogen-fixing ability, while three of the best isolates were capable of producing both IAA and gibberellin. Molecular analysis revealed that the best-performing isolates showed high similarity to Bacillus toyonensis and Bacillus cereus. These findings indicate that rhizosphere bacteria associated with foxtail millet have significant potential as biofertilizer candidates to support sustainable agriculture